2022
DOI: 10.1093/geroni/igab051
|View full text |Cite
|
Sign up to set email alerts
|

Driving Performance in Older Adults: Current Measures, Findings, and Implications for Roadway Safety

Abstract: Background and Objectives Over 10,000 people a day turn 65 in the United States. For many older adults, driving represents an essential component of independence and is one of the most important factors in overall mobility. Recent survey studies in older adults suggest that up to 60% of older adult drivers with mild cognitive impairment, and up to 30% with dementia, continue to drive. The purpose of this review is to provide a comprehensive and detailed resource on the topics of cognition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…This was highlighted during the pandemic when interactions with people outside the household were limited. Driving, which is often associated with greater independence in mobility [ 43 ], also provided a safer travel option during the pandemic than public transport, which instilled fear due to the potential risk of virus exposure [ 44 ]. The benefits of having good lower extremity performance and driving a car were more apparent in life-space mobility, which measures actual mobility.…”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted during the pandemic when interactions with people outside the household were limited. Driving, which is often associated with greater independence in mobility [ 43 ], also provided a safer travel option during the pandemic than public transport, which instilled fear due to the potential risk of virus exposure [ 44 ]. The benefits of having good lower extremity performance and driving a car were more apparent in life-space mobility, which measures actual mobility.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study has shown that many elderly drivers continue to drive despite deteriorating their health, leading to accidents (Jeong et al, 2023) and a higher risk of fatal crash involvement (Pitta et al, 2021). Changes in physical and cognitive abilities are critical aspects of healthy ageing that may directly affect older adults' driving performance (Toups et al, 2022). Anstey et al (2005) previously described that physical function, sensory function, and cognition are enabling factors that can predict driving safety among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Concluding our assessment suite was a robust cognitive evaluation that spanned multiple cognitive domains. This was essential in crafting a detailed cognitive profile for each participant, laying the groundwork for discerning correlations between specific cognitive abilities and their driving performance [40,41].…”
Section: Assessment Instrumentsmentioning
confidence: 99%